Etika Kerajaan Allah dalam Khotbah di Bukit sebagai Dasar Teologi Pendamaian Dunia - Grace Pasila (SAINT PAUL'S REVIEW, 2026)
Article history: Submit: May 15, 2026 Revised: Accepted: Published: Keywords: Ethics of the Kingdom, Sermon on the Mount, Theology of Reconciliation, Matthew 5-7, Conflict Kata kunci: Etika Kerajaan Allah, Khotbah di Bukit, Teologi Pendamaian, Matius 5-7, Konflik Abstract Conflict is an inevitable part of human life. Today’s world is faced with the emergence of various conflicts, such as social injustice, humanitarian crises, and international wars, making global peace difficult to achieve. This study seeks to examine the ethical values of the Kingdom of God in the Sermon on the Mount in Matthew 5–7 as the foundation for a theology of world peace. The study employs a qualitative method with an exegetical approach to the text of the Sermon on the Mount in Matthew 5–7 to identify the ethical values of the Kingdom of God that are relevant to human life. Biblical and systematic theological approaches are used to situate the exegetical findings within a broader theological framework. Data were obtained through a literature review, with the Bible as the primary source, as well as various theological literature discussing the ethics of the Kingdom of God and the concept of reconciliation. The research findings indicate that the Sermon on the Mount contains the ethical values of the Kingdom of God—such as love, forgiveness, justice, and peace—which are relevant as a foundation for peace amidst the various conflicts the world faces today. These values are transformative, not only in the structural realm but also in the personal realm, and they encourage Christians to actively become agents of peace in the world. Abstrak Konflik adalah hal yang tidak dapat dihindari dalam kehidupan umat manusia. Dunia sekarang ini diperhadapkan dengan munculnya berbagai konflik, seperti ketidakadilan sosial, krisis kemanusiaan, dan perang antarbangsa, sehingga pendamaian dunia masih sulit untuk diwujudkan. Penelitian ini berupaya mengkaji nilai-nilai etika Kerajaan Allah dalam Khotbah di Bukit dalam Matius 5–7 sebagai dasar Teologi pendamaian dunia. Penelitian menggunakan metode kualitatif dengan pendekatan eksegesis pada teks Khotbah di Bukit dalam Matius 5–7 untuk menemukan nilai-nilai etika Kerajaan Allah yang relevan bagi kehidupan manusia. Pendekatan Teologi biblika dan sistematis digunakan untuk menempatkan hasil eksegesis dalam kerangka Teologi yang luas. Data diperoleh melalui studi kepustakaan dengan Alkitab sebagai sumber utama, serta berbagai literatur teologi yang membahas mengenai etika Kerajaan Allah dan konsep pendamaian. Hasil penelitian menunjukkan bahwa Khotbah di Bukit memuat nilai-nilai etika Kerajaan Allah seperti kasih, pengampunan, keadilan, dan perdamaian, yang relevan untuk menjadi dasar perdamaian di tengah berbagai konflik yang dialami dunia sekarang ini. Nilai-nilai tersebut bersifat transformatif, tidak hanya pada ranah struktural tetapi juga pada ranah pribadi, serta mendorong umat Kristiani untuk secara aktif menjadi agen perdamaian di dunia.